Keanekaragaman, Kelimpahan dan Biomassa Biota Nektonik Indikator Terumbu Karang serta Jenis Ikan Lainnya di Kawasan Konservasi Pulau Gili Matra, NTB - Wiwid Andriyani Lestariningsih; Mahardika Rizqi Himawan; Aqil Anshori; Cakra Adiwijaya; Hotmariyah Hotmariyah; Martanina Martanina (LPPM Universitas Mataram, 2025)
Coral reefs are coastal ecosystems with high biodiversity that play a crucial role in aquatic productivity and the sustainability of fisheries resources. Nektonic biota are closely linked to coral reef conditions through their roles in trophic structure, energy cycling, and the regulation of ecosystem dynamics. This study aimed to analyze the diversity, abundance, and biomass of reef-associated nektonic indicator species and other reef fishes in the Gili Matra Marine Conservation Area, West Nusa Tenggara, Indonesia. Data were collected from March to June 2024 using the Underwater Visual Census (UVC) method along 70 m belt transects